2016
DOI: 10.31055/1851.2372.v51.n1.14421
|View full text |Cite
|
Sign up to set email alerts
|

Sistema Reproductivo de Trichloris (Poaceae, Chloridoideae, Chlorideae)

Abstract: Summary:Reproductive system of Trichloris (Poaceae, Chloridoideae, Chlorideae). Trichloris crinita and T. pluriflora are important native forage species with the potential to be domesticated and introduced to cultivation, but there is scarce basic information on their reproductive biology. The aim of this work was to determine the reproductive system of both plant species in populations coming from north-central Argentina. The following was proposed: 1) determine the reproductive system through the fruit/flowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 30 publications
0
11
0
1
Order By: Relevance
“…Altogether, the above data from the recent studies of Gutiérrez et al. () and Kozub et al. () provide conclusive evidence that Trichloris crinita reproduces mainly—if not exclusively—by sexual reproduction, and it self‐compatible and autogamous.…”
Section: Introductionmentioning
confidence: 69%
See 4 more Smart Citations
“…Altogether, the above data from the recent studies of Gutiérrez et al. () and Kozub et al. () provide conclusive evidence that Trichloris crinita reproduces mainly—if not exclusively—by sexual reproduction, and it self‐compatible and autogamous.…”
Section: Introductionmentioning
confidence: 69%
“…The combined data from embryo sac and FCSS analyses, reported by Kozub et al (2017), conclusively demonstrated that T. crinita seeds develop sexually (i.e., through double fertilization). In addition, pollination experiments performed in both studies concluded that T. crinita is self-compatible, because all the plants analysed produced seeds under self-pollination conditions (Guti errez et al, 2016;Kozub et al, 2017). In these studies, self-pollination was ensured by isolating inflorescences in moderately transparent paper bags 2 days prior to anthesis.…”
Section: Mode Of Reproductionmentioning
confidence: 99%
See 3 more Smart Citations